Social and Cultural Based Learning (Case study in TK At-Taqwa District. South Tarogong District. Garut) - Saepul, Saepul Rohim (GoResearch - Research & Publishing House, 2024)
Learning is a process carried out by educators and learners in a learning environment. Social and cultural aspects are two very important elements in the learning process in achieving learning goals that lead to the achievement of educational goals. Social and cultural-based learning is a learning that not only provides knowledge but learners participate actively in understanding and interpreting knowledge information in accordance with social and cultural backgrounds so as to provide more understanding to learners in accordance with their needs.